Comparison of Hay's Criteria with Nugent's Scoring System for Diagnosis of Bacterial Vaginosis. (12th June 2013) - Chawla, Rohit; Bhalla, Preena; Chadha, Sanjim; Grover, Sujatha; Garg, Suneela
Abstract : Although Nugent's criterion is considered as the gold standard for the diagnosis of bacterial vaginosis (BV), the method requires an experienced slide reader and considerable time and skill. In this study, we compared the method of Hay and Ison with Nugent's scoring criteria. Vaginal specimens were collected from a total of 213 women, presenting with or without the symptoms of vaginitis. Diagnosis of BV was done using Nugent' and Hay's method. Sensitivity, specificity, and predictive values for positive and negative test were calculated for Hay's method using Nugent's method as the gold standard. We diagnosed 70 cases (32.86%) of BV by Nugent's method and 87 (40.85%) cases by the Hay's method. Sensitivity, specificity, predictive value of positive result, predictive value of negative result, and Kappa value when evaluating Hay's criteria using Nugent's criteria as the gold standard were ≥97.2%, ≥88.1%, ≥80.4%, ≥97.1%, and ≥0.830, respectively, when Hay's grade II and/or Nugent's intermediate score were considered either as negative or positive or excluded. Using Nugent score for the intermediate group is the most difficult. Hay's method shows good agreement with the gold standard method of Nugent et al. and can be used as an alternative to Nugent's criteria in busy tertiary care hospitals.